Verbund von Industrie und Dienstleistungen wird enger - Rüdiger Hamm (Wirtschaftsdienst, 2012)
Nach der Drei-Sektoren-Hypothese gewinnt der Dienstleistungssektor gegenüber dem primären und sekundären Sektor immer mehr an Bedeutung. Die Rolle des sekundären Sektors ist jedoch nicht zu vernachlässigen, weil die Industrieunternehmen mit unternehmensorientierten Dienstleistern immer enger zusammenarbeiten und Teile ihrer Produktion auslagern. Rüdiger Hamm hat zu diesem Thema eine umfragebasierte Untersuchung im Rheinland vorgenommen. – – Structural change in highly developed countries is characterized by the increasing importance of the tertiary sector - especially production oriented services - at the expense of the secondary sector. The present paper analyzes the kinds of linkages between service industries and manufacturing branches using the results of a survey of fi rms carried out in parts of the German Rhineland. The results show that knowledge intensive services in particular help to strengthen the regions' export bases. Furthermore, service industries and manufacturing industries are closely and increasingly linked to each other. In this process manufacturing industries demand highly specialized services while service industries give innovative impulses, helping to increase industrial fi rms' competitive capability. Thus the importance of the manufacturing industry in this network is higher than statistical analysis is able to show. Regions are well advised, therefore, not to neglect the locational requirements of manufacturing industries.
Keywords: L16; O14; R12; 330; Industrieller Strukturwandel; Unternehmensdienstleistung; Rheinland; Deutschland